2014
DOI: 10.1128/genomea.00506-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Foot-and-Mouth Disease Virus Type A Circulating in Bangladesh

Abstract: The complete genome sequence of a foot-and-and mouth disease virus (FMDV) type A strain (BAN/GA/Sa-197/2013), isolated from Gazipur in Bangladesh, revealed an 84-nucleotide insertion within the 5′-untranslated region (UTR), a lengthened poly(C) tract, and amino acid substitutions at the VP1 region compared to the available genome sequence of the vaccine strain (GenBank accession no. HM854025).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…In Bangladesh, FMD occurs as endemic disease, and the frequency was progressively increasing all over the country since 2009 (Nandi et al 2013). FMDV serotype O was the only serotype that was reported to be circulating in Bangladesh in the late 2009 (Loth et al 2011) and after that both serotypes O and A were reported by our laboratory in late 2012 (Nandi et al 2013;Sultana et al 2014;Ullah et al 2014). However, the trend of FMDV serotype distribution in Bangladesh indicates that O, A and Asia1 were equally reported between 1958 and 1996, but in later studies, serotype Asia1 was not reported; rather, serotypes O and A were circulating (Loth et al 2011;Nandi et al 2013).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In Bangladesh, FMD occurs as endemic disease, and the frequency was progressively increasing all over the country since 2009 (Nandi et al 2013). FMDV serotype O was the only serotype that was reported to be circulating in Bangladesh in the late 2009 (Loth et al 2011) and after that both serotypes O and A were reported by our laboratory in late 2012 (Nandi et al 2013;Sultana et al 2014;Ullah et al 2014). However, the trend of FMDV serotype distribution in Bangladesh indicates that O, A and Asia1 were equally reported between 1958 and 1996, but in later studies, serotype Asia1 was not reported; rather, serotypes O and A were circulating (Loth et al 2011;Nandi et al 2013).…”
Section: Introductionmentioning
confidence: 64%
“…; Ullah et al . ). However, the trend of FMDV serotype distribution in Bangladesh indicates that O, A and Asia1 were equally reported between 1958 and 1996, but in later studies, serotype Asia1 was not reported; rather, serotypes O and A were circulating (Loth et al .…”
Section: Introductionmentioning
confidence: 97%
“…Among those, 206 samples were detected positive for FMDV RNA that were further analysed by amplifying the VP1 coding region using specific primers (for serotypes O, A and Asia1) to determine the serotypes of the virus. Selected 70 representative VP1‐specific amplicons covering all of the outbreak areas were sequenced and submitted to the NCBI GenBank database (Table ), of which, 30 sequences (FMDV serotype O‐8, serotype A‐15, serotype Asia1‐7) were published earlier (Ali et al., ; Nandi et al., ; Siddique et al., ; Sultana et al., ; Ullah, Siddique, Sultana, & Hossain, ; Ullah et al., ). Among the 34 outbreaks covered in this study, serotype O was responsible for 28 (82%) outbreaks, whereas 4 (12%) and 2 (6%) outbreaks were caused by serotypes A and Asia1, respectively—indicating serotype O as the dominant serotype.…”
Section: Resultsmentioning
confidence: 99%
“…FMDV circulating in India since 2005 belongs to genotype II, further classified into lineages C (group VIII) and D (group III) (Subramaniam et al., ). Genotype II has also been characterized from outbreaks in Bangladesh (Ullah et al., , ). Antigenic characterization suggests that the current local vaccine protects appropriately from this serotype (Sanyal et al., ; Subramaniam et al., ; WRLFMD, ).…”
Section: Endemic Pools In Asiamentioning
confidence: 99%